Spillovers and small spatial scale analyses: contributions from spatial economics - Fratesi, U.; Abreu, M.; Bond-Smith, Steven; Corrado, L.; Ditzen, J.; Felsenstein, D.; Fuerst, F.; Ioramashvili, C.; Kopczewska, K.; Monastiriotis, V.; Piras, G.; Quatraro, F.; et al. (2025)
This editorial introduces the seven papers included in this issue of Spatial Economic Analysis (SEA). The papers analyse two important topics in spatial economics. The first addresses the spillovers between units in space, specifically the phenomena through which different locations interact and the multiple channels through which these interactions take place. The second topic is related to the obtainment and processing of information at small spatial scales. The topics that are covered in the first theme are hence how distance influences venture capital (VC) investment decisions; the role of various proximities in innovation and regional knowledge production functions; the effects on local labour markets caused by what happens in other markets nearby; the use of different types of proximities and different distances at the same time in estimating spatial autoregressive model with autoregressive disturbances (SARAR) models. On the second topic the issue covers a new two-step technique to estimate small spatial scale synthetic data from microdata and aggregate statistics as an alternative to spatial microsimulation; the use of satellite data to estimate consumer confidence and expectations; and the use of disaggregated general equilibrium modelling based on the partial hypothetical extraction approach in input–output systems to estimate the effects of emergency aid.